CORPORATE CRIMINAL LIABILITY IN INDONESIA ON THE PERSPECTIVE OF COMPARISON - Muchammad Chasani (Universitas Negeri Semarang, 2017)
The regulation of corporate criminal liability in Indonesia's criminal justice system is basically a new and still debatable issue. It is said that because in the Criminal Code is not recognized and regulated explicitly about the corporation as a subject of criminal law. This is a natural thing since the WvS Criminal Code still adheres to the principle of